2021
DOI: 10.3390/nu13051719
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils, Pituranthos chloranthus and Teucrium ramosissimum, Chemosensitize Resistant Human Uterine Sarcoma MES-SA/Dx5 Cells to Doxorubicin by Inducing Apoptosis and Targeting P-Glycoprotein

Abstract: The multidrug resistance phenotype is a global phenomenon and causes chemotherapy failure in various cancers, such as in uterine sarcomas that have a high mortality rate. To overcome this phenotype, there is growing research interest in developing new treatment strategies. In this study, we highlight the potential of two essential oils from the Apiaceae family, Pituranthos chloranthus (PC) and Teucrium ramosissimum Desf. (TR), to act as chemopreventive and chemosensitizing agents against two uterine sarcoma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Moreover, studies have shown that doxorubicin in combination with Pituranthos chloranthus (PC) EO or Teucrium ramosissimum Desf. (TR) induces a synergistic effect in MES-SA/Dx5 cells and reduces the resistance index [ 58 ]. Al-Otaibi et al showed that the combination of Teucrium polium L. essential oil nanoemulsion and oxaliplatin had a synergistic effect with different p53 status colon cancer cells and induced a greater percentage of apoptosis [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have shown that doxorubicin in combination with Pituranthos chloranthus (PC) EO or Teucrium ramosissimum Desf. (TR) induces a synergistic effect in MES-SA/Dx5 cells and reduces the resistance index [ 58 ]. Al-Otaibi et al showed that the combination of Teucrium polium L. essential oil nanoemulsion and oxaliplatin had a synergistic effect with different p53 status colon cancer cells and induced a greater percentage of apoptosis [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, several EOs and their components are reported to exert anti-proliferative effects and induce apoptosis in cancer cells with minimal effects on non-transformed ones [ 27 , 28 ]. Moreover, since some of them work synergistically with commonly used anticancer drugs, they have been proposed as adjuvants in chemotherapy [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…They have been recognized as sources of many bioactive products that exhibit various biological and immunological activities, including anti-inflammatory, antibacterial, antibiofilm, antifungal and antiviral effects [ 16 , 17 , 18 , 19 ]. Furthermore, EOs have been shown to exert cancer cell targeting activity to increase the efficacy of commonly used chemotherapy drugs and to possess pro-immune functions [ 20 , 21 , 22 , 23 ]. Despite a large body of research indicating that EOs and their active compounds may have anticancer properties, not many successful drug formulations have reached the clinical stage.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Teucrium extract exert different protective effects against ethanol-induced ulcerogenesis [14]. Likewise, this species acts as chemopreventive and chemosensitizing agent against two uterine sarcoma cell lines, MES-SA and P-gp-overexpressing MES-SA/ Dx5 cells by a slight modulation of the cell cycle and its regulators, but also through a significant induction of apoptosis [15].…”
Section: Effects Of T Ramosissimum On Histological Changes Of Cecum A...mentioning
confidence: 99%